Incidence of tardive dyskinesia: a comparison of long‐acting injectable and oral paliperidone clinical trial databases. Issue 12 (31st October 2014) - Gopal, S.; Xu, H.; Bossie, C.; Burón, J. A.; Fu, D. J.; Savitz, A.; Nuamah, I.; Hough, D.
Summary: Background: To assess the tardive dyskinesia (TD) rate in studies of once‐monthly long‐acting injectable (LAI) paliperidone palmitate (PP) and once‐daily oral paliperidone extended release (Pali ER). Methods: Completed schizophrenia and bipolar studies for PP and Pali ER (≥ 6 month duration with retrievable patient‐level data) were included in this post hoc analysis. Schooler–Kane research criteria were applied using Abnormal Involuntary Movement Scale (AIMS) scores to categorise probable (qualifying AIMS scores persisting for ≥ 3 months) and persistent TD (score persisting ≥ 6 months). Spontaneously reported TD adverse events (AEs) were also summarised. Impact of exposure duration on dyskinesia (defined as AIMS total score ≥ 3) was assessed by summarising the monthly dyskinesia rate. Results: In the schizophrenia studies, TD rates for PP (four studies, N  = 1689) vs. Pali ER (five studies, N  = 2054), were: spontaneously reported AE, 0.18% (PP) vs. 0.10% (Pali ER); probable TD, 0.12% (PP) vs. 0.19% (Pali ER) and persistent TD, 0.12% (PP) vs. 0.05% (Pali ER). In the only bipolar study identified [Pali ER ( N  = 614)], TD rate was zero (spontaneously reported AE reporting, probable and persistent TD assessments). Dyskinesia rate was higher within the first month of treatment with both PP (13.1%) and Pali ER (11.7%) and steadily decreased over time (months 6–7: PP: 5.4%; Pali ER: 6.4%). Mean exposure: PP, 279.6 days; Pali ER, 187.2 days. Conclusions: Risk of TD with paliperidone was low (< 0.2%), regardless of the formulation (oral or LAI), in this clinical trial dataset. Longer cumulative exposure does not appear to increase the risk of dyskinesias.